MRI diagnosis of Baker cyst and significance of associated medical compartment knee osteoarthritis - Vasilevska, Violeta (Radiology and oncology (Ljubljana), 2008)
Background. The purpose was to evaluate the enlargement of the Baker cyst and the significance of medial compartment knee osteoarthritis.Patients and methods. In a period of two years we evaluated 66 patients with MRI signs of the Baker cyst and medial compartment knee osteoarthritis (median age 56 years, age range 34-84 years, 23 males and 43 females). One group was with MRIsigns of the large Baker cyst and the other one with the small Baker cyst. Following graded criteria for medial compartment were used: cartilage thickness, meniscus degeneration, bone marrow oedema, effusion. Lateral compartment was normal. Results. In the group with the large Baker cyst, 26/31cases (84%) had medial compartment cartilage loss. Eighteen from them hadassociated 3dh degree meniscal degeneration. Five/31 (16%) cases had only medial meniscus involvement. In the second group, 17/35 (48%) cases had cartilage loss, with 3dh degree meniscal degeneration was 14 (82%). In 18/35 (52%) cases only meniscus degeneration was present, 67% had 1st degree of meniscus degeneration. There was a statistically significant difference in thegroup with the distended Baker cyst between different degrees of medial meniscus degeneration. Conclusion. The size of the Baker cyst, as a soft tissue tumour, is strongly correlated with degenerative changes of the cartilage and with the degree of meniscus degeneration on the medial compartment of the knee joint.
Keywords: Bakerjeva cista; Diagnosis; hrustanec; Knee Joint; Kolenski sklep; Magnetic Resonance Imaging; Magnetna resonanca slikovna; Osteoarthritis; Osteoartritis; Popliteal Cyst; Poplitealna cista